Demands and Resources in Work Mediated by Digital Platforms: A Scoping Review of the Literature - Leite Carneiro, Laila; Tescari Medeiros, Giulia; Souza de Araújo, Irlan; Assolin Abou Abbas, Marian (Organizações & Sociedade, 2023)
Work arrangements with hiring mediated by digital platforms digiwork) have grown exponentially in recent years, both in the form of crowdwork and in the form of work on demand via app. However, there is still little systematization regarding knowledge about the elements that characterize this arrangement. Through a scoping review of the literature covering the period from 2005 to 2021, this study sought to identify the digiwork design characteristics, organizing it based on two specific categories: its requirements and the resources available to the worker. For that, it used the model of job demands and resources (JD-R) as a theoretical basis. After applying the inclusion and exclusion criteria, the 43 articles reviewed allowed for the identification of an important imbalance between the demands and resources present in digiwork. It also indicated many missing resources that make it difficult for workers to adequately deal with the demands of both the organization and the task. Among the most prominent demands, imprecision in labor categorization, surveillance via algorithmic management and self-management of risks stand out, while flexibility appears as the most cited resource present, and social protection as the most relevant resource absent. Taken together, the digiwork design characteristics may contribute to the worker's burnout process, in addition to interfering with their motivational process. This generates both suboptimal performance and damage to the worker’s health and well-being.